O impacto da comunicação colaborativa e do valor da marca na lealdade do comprador em relações b2b no setor de máquinas agrícolas - Bigóis, Larissa (2020)
The developed research had as objective to verify the impact of collaborative communication and the brand equity in the buyerʼs loyalty to the salesperson and in the buyerʼs loyalty concerning the company in the commercial channel of agricultural machinery. The research model proposed by the study contributed to analyze the previous business-to-business relationship in the level one marketing channel, in other words, manufacturer, distributor (resale), buyer (rural producer) in agribusiness universe. The public researched were 102 rural producer from the clientsʼ portfolio exclusive from the resales manufacturer. For this study, it was used Mohr, Fischer and Nevinʼs (1996) collaborative communication scale, Sneider Castillo and Ortegón Cortazarʼs (2016) brand equity scale, and Palmatier, Scheer and Steenkampʼs (2007) scale of salespersonʼs loyalty and companyʼs loyalty. This quantitative research has tested the hypothesis through partial least squares structural equation modeling. The results showed that the bidirectionality facet has a positive impact on the buyerʼs loyalty concerning the salesperson and the brand equity has a positive impact on the companyʼs loyalty. The analyze also reveals that the rural producers are more loyal to the manufacturer of agricultural machinery, when compared to the salespersons of exclusive resales. According to this result, it is assumed that the relationship between the salesperson and the rural producer is based on transactional and non-relational exchanges. This study has contributed to the advance of interorganizational relationships theory by integrating the measures regarding the collaborative communication and brand equity strategies. Furthermore, the contribution of this study is to analyze separately the buyerʼs loyalty to the specific salesperson and the buyerʼs loyalty to the selling company.